2019 IEEE/CVF Conference on Computer Vision and Pattern Recognition (CVPR) 2019
DOI: 10.1109/cvpr.2019.01079
|View full text |Cite
|
Sign up to set email alerts
|

Selective Sensor Fusion for Neural Visual-Inertial Odometry

Abstract: Deep learning approaches for Visual-Inertial Odometry (VIO) have proven successful, but they rarely focus on incorporating robust fusion strategies for dealing with imperfect input sensory data. We propose a novel end-to-end selective sensor fusion framework for monocular VIO, which fuses monocular images and inertial measurements in order to estimate the trajectory whilst improving robustness to real-life issues, such as missing and corrupted data or bad sensor synchronization. In particular, we propose two f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
129
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(129 citation statements)
references
References 36 publications
0
129
0
Order By: Relevance
“…VINet firstly tackled VIO in a supervised manner. Chen et al [Chen et al, 2019] exploited two masking strategies for visual-inertial sensor fusion.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…VINet firstly tackled VIO in a supervised manner. Chen et al [Chen et al, 2019] exploited two masking strategies for visual-inertial sensor fusion.…”
Section: Related Workmentioning
confidence: 99%
“…With the development of CNN and RNN, various learningbased VO or VIO methods have been proposed. Although many supervised methods [Wang et al, 2018, Chen et al, 2019 have been revealed more competitive than traditional methods, the demands of a large number of labeled data, i.e., the ground truth poses acquired from high-precision devices, limit the application of the technology. Self-supervised methods [Shamwell et al, 2018, Han et al, 2019 release the pressure of collecting large quantities of ground truth, but they still require other expensive data, e.g., depth map, which degrades the flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…One of the key steps in multimodal machine learning is the multimodal fusion, with the aim at integrating features of multiple modalities for enabling more accurate and robust performance. Three types of fusion strategies (i.e., early, late, and hybrid fusion) are the commonly used techniques for multimodal feature fusion [2][12] [5]. Our proposed adaptive feature fusion strategy is particularly related to late fusion with a focus on the selection mechanism in order to choose the most relevant feature representations from different modalities, meanwhile it can avoid useless or misleading information.…”
Section: Multimodal Machine Learningmentioning
confidence: 99%
“…, ∈ { , , }, and ∈ [0, 1] representing the score for individual feature extracted from different modalities. Instead of re-weighting each feature by the corresponding score, we apply a stochastic fusion method [5] to select the feature from different modalities.…”
Section: Multimodal Fusionmentioning
confidence: 99%
“…The optimization-based strategy is commonly more reliable than filtering-based and is more robust to outliers. Most recently, deep learning based-VINS [20][21][22] have employed the Convolutional Neural Networks (CNNs) and Long Short Term Memory (LSTM) networks [23] architecture into an end-to-end learning process [24] to handle vision and inertial data simultaneously. The evaluations are sufficient but less precise compared to the model-based systems.…”
Section: Introductionmentioning
confidence: 99%